(Deliberative) Democracy in the Times of the Anthropocene - Edoardo Greblo (Scienza & Politica, 2025)
It has been evident for some time that democracies face significant challenges when addressing the issue of climate change. This has given rise to a trend that could be termed «eco-authoritarian», based on the belief that the magnitude of the problem may require, in certain cases, the suspension of some democratic rules. Contrary to this orientation is the so-called «libertarian paternalism», which argues that it is possible to structure decision-making in a way that encourages individuals to make environmentally-oriented choices without impinging on their freedom. The thesis of the article is that a response to the challenges posed by both sides can be found in a deliberative conception of democracy, which draws from the mutual exchange between the institutional formation of will and an informal formation of opinion and ideas.